Pengembangan Media Scrapbook Menggunakan Model Discovery Learning Pada Pembelajaran Tematik Di Kelas IV SD Negeri 05 Pasar Tiku Tanjung Mutiara Kabupaten Agam - Jendriadi; Marlina, Meri (Jurnal Riset Pendidikan Dasar Dan Karakter, 2023)
This research was motivated by deficiencies in the thematic learning process for science material, it is known that in the learning process using visual learning media, it has not yet had an impact on the enthusiansm of students in participating in learning and the media used has not created a critical and active thinking attitude for students. This study aims to determine the development, validity, practicality and effectiveness of scrapbook media using the Discovery Learning model in science lessons in grade IV Elementary School. This type oresearch is R&D using a 4D model (define, design, development, and dissemination). At the dissemination strage, a trial was conducted on 10 elementery school fourth grade students. The data collection instrument in this study was in the form of a validation sheet (for material experts, linguists, and media experts). Practical instruments are in the form of a questionnaire of educators, students and effectiveness seen from student learning outcomes. The results showed that the Scrapbook media using the Discovery Learning model in science lessons on the life cyle of living things in grade IV elementry school was very valid, with a material expert validation score of 75% with a valid category, linguist validation with a score of 93,18% with a very valid category. And the average value of the overall validation is a score of 86,59% (very valid) for practicality results from 1 educator, an average score of 86,1% was obtained with the very practical assesment criteria, while for the practicality of 10 students the average score was 91.22% with very practical criteria. For the results of the effectiveness off getting an average value of 90,00% with very effective criteria. So it can be concluded that the development of scrapbook media using the Discovery Learning model in grade IV elementary School is very valid, practical, and effective